MEATSHOP – ONLINE BUTCHERS (CIPEEX, 2024)
The planned platform will be called Meat Shop, and the proposal is that it can innovate thebutchery business by providing a new way of buying meat and meat products. In order toimprove the way tasks are carried out on a daily basis, apps are becoming more and morecomplete in order to meet all the needs of their users quickly and intuitively. However, thebutcher's market is underdeveloped in this respect and ends up being limited to face-to-faceand/or telephone orders, making the sale of these products more bureaucratic. Foremost, asurvey and statistical analysis were carried out in order to understand the needs of themarket, and around 95% of the people interviewed said that they go to the butcher's inperson to buy meat, and 42% said that going to the butcher's takes up a lot of their time on adaily basis. That's why this software aims to provide customers in this sector with an easyand personalized shopping experience. In it, problems such as noises in communication,which often hinder purchases in the traditional method, will not occur. In addition, it will speedup the ordering process; customers will be able to view the products available in stock,repeat orders already placed using a purchase history, schedule future orders, receive tipson favorite cuts, compare prices between establishments, and track the progress of theirdeliveries. In addition, the project's requirements were gathered, and an MVP (minimumviable product) was created to meet the users' main needs, in order to later implement thefunctionalities that were initially considered unnecessary but, according to user feedback,could be considered useful and attractive at a certain point. The platform will be divided into afew stages: choosing the establishment, cut, quantity, delivery address, payment method andevaluation. In this way, it can be concluded that the idea will bring several benefits to thesector, such as: an increase in sales, since even with little time for daily tasks, people will beable to make their purchases with a few clicks and quickly; a reduction in the rate of wrongorders, since communication noise is almost non-existent in app-based purchases; speedand agility in everyday life, since you don't have to go to the location to order, avoiding trafficand other related problems; greater customer reach, since many people don't like to go veryfar to buy their products, while the application does not have this problem. The software isstill under development but has made good progress and is currently at the design stage:creating the visual identity and layout of elements, functionality tests and research into thebest way to organize the flow of information. There is still a lot to do, but it has made solid